Grasping the concept of value: Exploring students’ economic and financial literacy in citizenship education - Björklund, Mattias; Tväråna, Malin; Jägerskog, Ann-Sofie; Strandberg, Max (JSSE - Journal of Social Science Education, 2022)
Purpose: To explore student’s understandings of financial literacy and economics issues with an aim to inform future teaching designs. Design/methodology/approach: Phenomenography and variation theory has been used to analyze students’ understanding of a concept found in both financial and economic contexts, namely value. Findings: Students need to discern that value is attributed, related to scarcity and to other values in order to elaborate their understanding. Thus, teaching also needs to address these issues. Research implications: A social science framing of financial literacy and economics can facilitate a teaching that aims for the development of students’ critical thinking and future ability to make informed choices.